New series of Portuguese population and employment, 1950-2007: implications for GDP per capita and labor productivity - Amaral, Luciano (2009)
The two most important international databases with Portuguese GDP per capita and productivity from the 1950s onwards (GGDC and Ameco) offer two contrasting pictures of its evolution, especially during the slowdown of 1973 to the mid-1980s. The main problem is the low quality of the underlying data for population and employment. This paper offers new estimates for population and employment and recalculates GDP per capita and productivity between 1950 and 2007. Although confirming the main idea advanced in GGDC (a similar slowdown of GDP per capita and productivity), the series are different, and should be viewed as the new benchmark for the Portuguese economy.